Komitmen Pernikahan dengan Kepuasan Pernikahan di Desa Mulyo Agung - Albadh Muhammad; Muhamad Uyun; Eko Oktapiya Hadinata (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to determine the relationship between marriage commitment and marriage satisfaction in Mulyo Agung village. The population are 420, and a sample of 204 people are drawn based on the cluster random sampling technique. Data was collected using the marriage satisfaction scale based on aspects of marriage satisfaction according to Olson & Fowers. Also, the scale of marriage commitment based on aspects of marriage commitment according to Adam & Jones. The analytical method used is simple regression analysis which shows the number r of 0.503 with the value r 2 = 0.249 with p = 0,000 where p <0.05. So that the hypothesis is proven that there is a positive relationship between Marriage Commitment and Marriage Satisfaction in Mulyo Agung Village. Researcher suggest to the next researchers to examine other variables that affect marital satisfaction with a larger number samples and complete theories.